STRUKTUR BIAYA USAHA BUDIDAYA LEBAH MADU DI DESA KUAPAN KECAMATAN TAMBANG KABUPATEN KAMPAR (Kasus Usaha Madu “Mekar Sari”) - Ilma Satriana Dewi (DINAMIKA PERTANIAN, 2022)
Communities in the Riau area have started cultivating honey bees both traditionally and in a modern way. However, the development of honey bee farming (Apis cerana) is currently still not progressing even though the business has been running for quite a long time. This could have been caused by several things, namely poor business management, starting from cultivation activities to quite high production costs. This study aims to analyze breeder characteristics and profiles, analyze production costs, production, income, and business efficiency, and analyze the cost structure of the "Mekar Sari" honey bee business. This research was conducted using a survey method, namely in the honey bee (Apis cerana) cultivation business in Kuapan Village, Tambang District, Kampar Regency. The analytical method used in this study is descriptive qualitative and quantitative analysis. The results showed that the breeders made the honey bee business a side business. The farmer is 30 years old and belongs to the productive age, his last education is a Bachelor of Animal Husbandry (S1), 10 years of farming experience, and has 3 dependents (1 wife and 2 children). The profile of the honey bee business "Mekar Sari" started as a group business funded by government assistance, but many members withdrew so the number of honey beekeepers decreased. Only 1 member of the group survives and continues the "Mekar Sari" honey business to this day. The production cost used in the "Mekar Sari" honey business is IDR 77,123,362/year, with a production of 800 kg. Gross income of IDR 120,000,000/year, and net income of IDR 42,876,638/year, and an efficiency of 1.55. The cost structure of the honey bee business "Mekar Sari" consists of the cost of production facilities with a percentage of 91.74%, labor costs of 2.77%, and equipment depreciation costs of 5.44%.